UPAYA GURU DALAM MEMBINA AKHLAK SISWA MADRASAH TSANAWIYAH MIFTAHUL JANNAH BANGKUNAT PESISIR BARAT - Samhan; Taqwatul Uliyah; Riskun Iqbal (UNISAN JURNAL, 2024)
Moral education is so broad that it is impossible if moral education is only the responsibility of the moral teacher. Therefore, the idea emerged about the importance of the hidden curriculum in moral education, which is not explicitly written in the curriculum. This opinion assumes that all activities of teachers, parents, society and the state are expected to help and provide extra services in helping to achieve the goals of moral education. Teachers can relate problems in their field of study to morals. This thesis examines teachers' efforts to develop morals in MTs students. Miftahul Jannah Bangkunat. The aim of the research in this thesis is to determine the efforts of teachers in developing the morals of students at Madrasah Tsanawiyah Miftahul Jannah Bangkunat Pesisir Barat. This type of research is field research using a qualitative descriptive approach. In data collection, data collection techniques were used in the form of purposive sampling, snowball sampling. The method used in data collection is the observation method as the main method, the interview method and the documentation method as the supporting method. Meanwhile, qualitative analysis was used for data analysis with stages of data reduction, data presentation and drawing conclusions. Conclusions are drawn by inductive thinking. The results of the research show that the teacher's efforts in developing the morals of MTs students. Miftahul Jannah Bangkunat, namely through habituation, example, punishment, advice, learning, controlling, coaching, giving assignments, lectures, questions and answers, stories, targhib (motivating love of goodness), tarhim (prohibition), bil hikmah (wise) and deliberation. However, Islamic religious education teachers have not carried out evaluations, that is, they have not brainstormed, identified problems, analyzed problems using certain techniques, looked for alternative solutions, determined problem solving actions, planned actions, taken actions and evaluated actions.